Infusing cognitive neuroscience into the clinical neuropsychology of memory. (April 2020) - McAndrews, Mary Pat; Cohn, Melanie; Gold, David A
Highlights: There is a limited translation of experimental memory constructs into clinical practice. Associative memory indexes hippocampal dysfunction across neurological disorders. There are some promising initiatives in diagnosis and predicting disease trajectory. Intervention trials are underway, inspired by cognitive neuroscience principles. Establishing clinical utility will require meeting psychometric standards. Abstract : The cognitive neuroscience of episodic memory originated with patient studies, including the transformational research with HM following bilateral temporal lobe excision for epilepsy. While functional imaging studies have become prominent in neurocognitive research on memory, important insights into aspects of memory representation and processes have been established, further articulated, and corroborated by studies with patients. Translation of these theoretical insights back into the clinic is limited, but neuropsychology has begun to capitalize on findings from cognitive paradigms that better specify memory processes and underlying neural networks to enhance diagnosis, prognosis, and validation of therapeutic strategies. This review highlights some of these contributions, focussing on three neurological disorders to encourage further seamless integration of clinical and cognitive neuroscience research.